Desarrollo de una herramienta digital que permita al departamento de ingeniería biomédica de la clínica nueva el lago apoyar los procesos de gestión tecnológica. (2023)
Biomedical technological management is a set of actions aimed at ensuring proper daily activities within a clinic regarding medical equipment, particularly in processes such as equipment maintenance. Therefore, a digital tool was developed for Clínica Nueva el Lago, specifically for the technological management area. This tool allows for the consultation and editing of information related to medical equipment in the institution through a database created for inventory management. Additionally, it enables the generation of digital reports for preventive and corrective maintenance, delivery and departure records, thus facilitating access to information throughout the institution.